Formulation of kinematics and gait locomotion for Hyper-Redundant robot. (2022) - Abhishek, Kumar; Kumar Dalla, Vijay
Abstract: Robots with numerous excess degrees of freedom (DOF) are known as hyper-redundant. These robots resemble snakes or tentacles are suitable for use in extremely constrained situations as well as new modes of locomotion. This work discusses kinematic analysis of hyper-redundant (H-R) systems over solid terrain. The analysis is based on travelling wave gait which is used to model variety of locomotion for example: locomotion of flatworm or inchworm. The H-R locomotion describes displacement generated from internal bending or twisting of its mechanism. Kinematics of gait is formulated for both extensible and non-extensible H-R locomotion. Its kinematics is modelled using differential geometry of planar curves. Flatworm and inchworm locomotion has been idealized using travelling wave gait models. An H-R precise manipulation method of grasping wave is also introduced.